Effects of in-feed additives on performance, gut microbe ecology, and antimicrobial susceptibility of enterobacteria on nursery pigs - Williams, Hayden Ervin (Kansas State University, 2017)
Two experiments using a total of 720 nursery pigs were used to determine the effects of Elarom SES, in-feed antibiotics, zinc, or copper on nursery pig growth performance and fecal consistency. Two experiments using a total of 1,534 nursery pigs were used to determine the effects of formaldehyde inclusion, lysine level, and synthetic amino acid inclusion on nursery pig performance, amino acid utilization, and gut microbial community. One experiment using a total of 300 nursery pigs were used to determine the effects of chlortetracycline (CTC) or a probiotic inclusion on nursery pig growth performance and antimicrobial susceptibility. Experiment 1 determined the effect of Elarom SES, in-feed antibiotics, or zinc on nursery pig performance and fecal consistency. The addition of Elarom SES or ZnO alone reduced ADG, but G:F was poorest when all three additives were fed in combination. Addition of in-feed antibiotics increased ADG and G:F throughout the study. Experiment 2 determined the effects of Elarom SES or copper inclusion on nursery pig performance and fecal consistency. The addition of Elarom SES or increasing copper did not provide consistent benefits in performance. In both experiments, there were no individual or overall treatment effects or treatment × day interactions observed for fecal consistency. Experiment 3 compared the effects of formaldehyde source and lysine level on nursery pig growth performance. Regardless of source or lys level, the inclusion of formaldehyde in nursery pig diets marginally reduced ADG and resulted in poorer G:F. Experiment 4 compared the effects of formaldehyde and synthetic amino acid inclusion level on nursery pig growth performance, amino acid utilization, and gut microbial community. The inclusion of Sal CURB in diets reduced ADG and ending BW while inclusion decreased ADFI. ADFI response was dependent on synthetic amino acid level in the diet. Sal CURB inclusion in diets reduced total and available lysine, but reduced bacterial microflora in treatment feed. Experiment 5 determined the effects of CTC or a probiotic on nursery pig performance and antimicrobial susceptibility. The addition of CTC to diets improved ADG, ADFI, and ending BW. The addition of Poultry Star improved ADFI and d 14 BW, but benefits did not carry throughout the study.
Keywords: Feed additive; Formaldehyde; Microbiome; Nursery pig; Antimicrobial resistance